David Smith (Solomon R. Guggenheim Museum, 1969)
Catalog prepared for a retrospective loan exhibition held in 1969 at the Solomon R. Guggenheim Museum, New York, the Dallas Museum of Fine Arts, and the Corcoran Gallery, Washington, D. C.